2022
DOI: 10.1186/s13690-022-00893-4
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of surgical mask in young healthy subjects on cardiopulmonary function and muscle performance: a randomized crossover trial

Abstract: Objective To explore the impacts of surgical mask in normal subjects on cardiopulmonary function and muscle performance under different motor load and gender differences. Design Randomized crossover trial. Setting The Fifth Affiliated Hospital of Guangzhou Medical University, June 16th to December 30th, 2020. Participants Thirty-one college students (age: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Koseoglu et al also reported increases in dyspnea, itching, ear pain, and headache induction ( 90 ). Ou et al reported negative impact on the ventilation function of exercise with mask on in young healthy subjects ( 91 ). It is also important point that the weight of the surgical mask increased during the exercise ( 92 ).…”
Section: Mask Rules (Mandate): Review Of Side Effectsmentioning
confidence: 99%
“…Koseoglu et al also reported increases in dyspnea, itching, ear pain, and headache induction ( 90 ). Ou et al reported negative impact on the ventilation function of exercise with mask on in young healthy subjects ( 91 ). It is also important point that the weight of the surgical mask increased during the exercise ( 92 ).…”
Section: Mask Rules (Mandate): Review Of Side Effectsmentioning
confidence: 99%
“…Studies in healthy volunteers have demonstrated an increase in perceived exertion (work of breathing) during sub-maximal exercise, [12][13][14] likely due to increased resistance to airflow, which at maximal effort impedes numerous physiologic parameters including oxygen consumption and endtidal CO 2 . 15,16 Bronchoscopy can be a physiologically demanding procedure, patients with respiratory disease are at significant risk of greater perturbations in physiology than described in health adults. If barrier masks are to be used in this group, then close monitoring of respiratory status during and after the bronchoscopy is imperative.…”
mentioning
confidence: 99%
“…Despite this, an elevation in end‐tidal CO 2 was noted, as was an association with hypoxia in patients with resting low SaO 2 . Studies in healthy volunteers have demonstrated an increase in perceived exertion (work of breathing) during sub‐maximal exercise, 12–14 likely due to increased resistance to airflow, which at maximal effort impedes numerous physiologic parameters including oxygen consumption and end‐tidal CO 2 15,16 . Bronchoscopy can be a physiologically demanding procedure, patients with respiratory disease are at significant risk of greater perturbations in physiology than described in health adults.…”
mentioning
confidence: 99%